The Role Of The Millennial Generation In Da'wah Journalism In The Digital Age - Retna Dwi Estuningtyas; Siti Nuri Nurhaidah; Zamakhsyari Abdul Majid; Abdul Hamid (CV. Syntax Corporation Indonesia, 2023)
The development of da'wah in the present, known as the digital era, has been increasingly advanced in the use of da'wah media. The millennial generation, as a generation that is responsive to technology, does not miss using internet media to convey da'wah messages with its journalistic da'wah. One of the selected media is social media, this is because social media users are increasing every year in Indonesia. In the use of social media and internet networks, communication that is built in da'wah journalism certainly follows the journalistic code of ethics and remains consistent in spreading the function of da'wah journalism as prophetic journalism.